2011
DOI: 10.2337/db11-0739
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Hepatic Metabolism and Hyperaminoacidemia in Mice Deficient in Proglucagon-Derived Peptides

Abstract: Glucagon is believed to be one of the most important peptides for upregulating blood glucose levels. However, homozygous glucagon–green fluorescent protein (gfp) knock-in mice (Gcggfp/gfp: GCGKO) are normoglycemic despite the absence of proglucagon-derived peptides, including glucagon. To characterize metabolism in the GCGKO mice, we analyzed gene expression and metabolome in the liver. The expression of genes encoding rate-limiting enzymes for gluconeogenesis was only marginally altered. On the other hand, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 47 publications
6
53
0
Order By: Relevance
“…A recent study showed that a patient with a GCGR splice mutation had hyperaminoacidemia (Larger et al, 2016) while glucagonoma patients without known GCGR mutations present with hypoaminoacidemia from excess glucagon action. It is possible that elevated Q plays a role in patients with GCGR inactivating mutations as Gcgr-/- mice and other mouse models of interrupted glucagon signaling develop α-cell tumors as they age (Yu et al, 2011; Yang et al, 2011; Watanabe et al 2012; Takano et al, 2015). In animal studies where GCGR antibodies are withdrawn or where glucagon is administered, α-cell mass reduces over time suggesting tight responsiveness to AA signaling (Gu et al, 2009; Okamoto et al, 2015; Petersson and Hellman, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a patient with a GCGR splice mutation had hyperaminoacidemia (Larger et al, 2016) while glucagonoma patients without known GCGR mutations present with hypoaminoacidemia from excess glucagon action. It is possible that elevated Q plays a role in patients with GCGR inactivating mutations as Gcgr-/- mice and other mouse models of interrupted glucagon signaling develop α-cell tumors as they age (Yu et al, 2011; Yang et al, 2011; Watanabe et al 2012; Takano et al, 2015). In animal studies where GCGR antibodies are withdrawn or where glucagon is administered, α-cell mass reduces over time suggesting tight responsiveness to AA signaling (Gu et al, 2009; Okamoto et al, 2015; Petersson and Hellman, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Imai et al (32) have demonstrated that signals from the liver mediated through the autonomic nervous system regulate β-cell proliferation. In addition, it has been demonstrated that hepatic metabolism, especially amino acid metabolism, is remodeled in animal models deficient in glucagon action (33,34). Such metabolic and/or neural signals from extraislet organs also may be involved in altered proliferation and function of α-cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of reduced glucagon secretion or action on glucose homeostasis has been evaluated using several pharmacological and genetic approaches: (a) PC2 knockout mice (Pcsk2 À/À ) which are unable to produce mature glucagon because they lack prohormone convertase 2 (Webb et al 2002), (b) glucagon-GFP knockin mice in which GFP has been inserted within the pre-proglucagon gene leading to lack of glucagon production (Watanabe et al 2012;Hayashi 2011;Hayashi et al 2009), (c) pancreas-specific aristalessrelated homeobox (ARX) knockout mice which lack glucagon-producing α-cells (Hancock et al 2010), (d) liver-specific Gsα knockout mice in which the glucagon action in the liver is specifically blocked , (e) glucagon receptor knockout mice (Parker et al 2002;Gelling et al 2003), (f) liver-specific glucagon receptor knockout mice (Longuet et al 2013), (g) immunoneutralization of endogenous glucagon with glucagon antibodies (Brand et al 1994), (h) reduction of glucagon receptor expression by antisense oligonucleotide (Liang et al 2004;Sloop et al 2004), and (i) glucagon receptor antagonists (Cho et al 2012;Johnson et al 1982;Qureshi et al 2004;Christensen et al 2011). A vast majority of these studies concluded that anti-glucagon strategies improve glucose tolerance and attributed the improvement to a decreased glucagon action.…”
Section: Therapies Targeting Glucagon Actionmentioning
confidence: 99%